(untitled) (World Economics and Finance Bulletin, 2023)
The research aims to test the influence relationship of the variables of current studyPrepare professional competenciesin dependent variable by dividing it intoSatisfaction with the tour guide service as a dependent variable for a sample ofGuests at "Kilo Ali Beg Resort", in Erbil Governorate Indeed (340) a questionnaire distributed to tourists, distributed to them exclusively and comprehensive to surveytheir opinionsAbout the availability of the researched variable stolidentify the relationships targeted by the study, so receive from them (310) and when unpacked excluded (10) Including that it is not valid for statistical analysis to be the study sample(300), and these variables interacted to form general framework of the research, and the main and sub-hypotheses emanated from them in order to achieve research objectives